2015
DOI: 10.1002/pds.3776
|View full text |Cite
|
Sign up to set email alerts
|

Trends in opioid prescribing and co-prescribing of sedative hypnotics for acute and chronic musculoskeletal pain: 2001-2010

Abstract: Opioid prescribing for acute and chronic musculoskeletal pain increased from 2001 to 2010, plateauing from 2006 to 2010 for chronic pain visits. Co-prescribing of opioids and sedative hypnotics is common and may represent a target for interventions to improve the safety of opioid prescribing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
80
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(80 citation statements)
references
References 26 publications
(73 reference statements)
0
80
0
Order By: Relevance
“…That is, we found support for increased risk of long-term opioid therapy in adulthood and youth related to SUDs, suicide attempts or other self-injury, motor vehicle crashes, and depressive, anxiety, and sleep disorders, as well as a broad array of psychoactive medications—including benzodiazepines [34]. Additionally, we found that the strongest risk for receipt of long-term opioids was associated with OUD diagnoses and treatment with buprenorphine or naltrexone.…”
Section: Discussionmentioning
confidence: 66%
“…That is, we found support for increased risk of long-term opioid therapy in adulthood and youth related to SUDs, suicide attempts or other self-injury, motor vehicle crashes, and depressive, anxiety, and sleep disorders, as well as a broad array of psychoactive medications—including benzodiazepines [34]. Additionally, we found that the strongest risk for receipt of long-term opioids was associated with OUD diagnoses and treatment with buprenorphine or naltrexone.…”
Section: Discussionmentioning
confidence: 66%
“…Available death certificate reports seem unclear, but perhaps one third of death certificates listing overdose with an opiate as a cause of death also lists a benzodiazepine, Z hypnotic, or barbiturate as a cause of death (retrieved from CDC Wonder). An opioid prescription is more likely to lead to overdose when a hypnotic is prescribed 3 . There have also been several thousand yearly reported overdoses involving a hypnotic in which an opiate was not involved.…”
Section: Risks Of Hypnotic Drugsmentioning
confidence: 99%
“…This finding was not confirmed by one Taiwanese study 34 , but another Taiwanese study focusing on patients with sleep disturbances found that use of zolpidem was associated with 62%–91% increased hospitalizations for serious infections 35 . A Taiwan study of patients with chronic obstructive pulmonary disease found highly significant odds ratios associated with benzodiazepine use of 9.3 for pneumonia, 10.4 for acute chronic obstructive pulmonary disease (COPD) exacerbation, 45.0 for acute respiratory failure, and 18.6 for cardiopulmonary arrest; whereas the odds ratios for "Z" drugs such as zolpidem were of almost similar magnitude 3 . In confirmation, note in the Geisinger Health Study supplement, Table 7 16 , mortality hazard ratios were likewise specifically elevated among hypnotics users with COPD.…”
Section: Hypnotics Can Cause Serious and Potentially Lethal Infectionsmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11] Greater opioid prescribing contributed to increased opioid availability for abuse and overdose. [12][13][14] Primary care physicians (PCPs) and internists prescribe the majority of opioids.…”
Section: Introductionmentioning
confidence: 99%